1995
DOI: 10.1259/0007-1285-68-807-266
|View full text |Cite
|
Sign up to set email alerts
|

Cervical lymphadenopathy: ratio of long- to short-axis diameter as a predictor of malignancy

Abstract: The purpose of this study was to evaluate short- and long-axis diameters of enlarged cervical lymph nodes with ultrasonography and to determine whether the long-to-short axis (l/s) ratio is a valid diagnostic parameter in the differentiation between benign and malignant nodal disease. 730 enlarged cervical lymph nodes in 285 patients were examined with ultrasound. The short- and the long-axis diameters of each enlarged node were measured and the l/s ratio calculated. Definite diagnoses of the nodes were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
107
5
8

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(127 citation statements)
references
References 13 publications
7
107
5
8
Order By: Relevance
“…They noted the decrease of false positive results from 63% to 5% using the L/S ratio. Sarvanan et al [17] have showed similar sensitivity (94.44%) and higher specificity (100%) than that reported by Steinkamp et al [18].…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…They noted the decrease of false positive results from 63% to 5% using the L/S ratio. Sarvanan et al [17] have showed similar sensitivity (94.44%) and higher specificity (100%) than that reported by Steinkamp et al [18].…”
Section: Discussionmentioning
confidence: 60%
“…A sensitivity of 82.9% and a specificity of 89.66% for CT scanning and a sensitivity of 97.1% and a specificity of 93% for ultrasound scanning. Steinkamp et al [18] reported 95% sensitivity of the L/S ratio as well as a specificity of 95% compared with 37% for the long axis method and 86% for the transverse diameter method. They noted the decrease of false positive results from 63% to 5% using the L/S ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the follow-up of patients with breast carcinoma and patients with head and neck tumors, ultrasound of the regional lymph nodes is of great importance because early detection of lymph node disease also influences the prognosis of these malignancies. 16,17 Computer tomography of the lymph nodes has been shown to be less adequate, because the examination is performed in one transverse section only. 18 Early detection of subcutaneous and regional metastases in patients with cutaneous melanoma seems to be critical for the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Using these imaging modalities, the criteria for diagnosing metastatic nodes is mainly dimensional. Measurements include the minimum transaxial diameter, the maximum transaxial diameter or a ratio between the maximum longitudinal and the maximum axial diameters (3)(4)(5)(6)(7). Other parameters, such as morphological criteria or the pattern of enhancement, are regarded as less important in this setting.…”
mentioning
confidence: 99%